2019
DOI: 10.1109/taffc.2017.2753777
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for the Automatic Extraction and Generation of Non-Verbal Signals Sequences Conveying Interpersonal Attitudes

Abstract: Depending on their application, Embodied Conversational Agents (ECAs) must be able to express various affects or social constructs such as emotions or social attitudes. Non-verbal signals, such as smiles or gestures, contribute to the expression of attitudes. Social attitudes affect the whole behavior of a person: as Scherer puts it, they are "characteristic of an affective style that colors the entire interaction" [1]. Moreover, recent findings have demonstrated that non-verbal signals are not interpretated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Attitudes are expressed through both verbal and non-verbal behaviors. Several works showed that combining both non-verbal and verbal modalities may lead to better attitude recognition [26], [24]. Our model has only focused on the non-verbal behavior for attitude expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attitudes are expressed through both verbal and non-verbal behaviors. Several works showed that combining both non-verbal and verbal modalities may lead to better attitude recognition [26], [24]. Our model has only focused on the non-verbal behavior for attitude expression.…”
Section: Discussionmentioning
confidence: 99%
“…A pattern is a sub-sequence that occurs frequently in the dataset. Sequence mining has been applied in a wide range of reallife applications in many domains such as marketing [35], bioinformatics [49], text mining [50] and human behavior analysis [24], [44]. In this Section, we present the different algorithms of sequence mining.…”
Section: Temporal Sequence Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…Wireless Communications and Mobile Computing based on visual recognition, which uses the motion and expression capture technology in visual recognition to render the animation task action expressions, which improves the efficiency and quality of 3D animation production [13]. Most design companies currently use three main types of 3D animation material management platforms, stand-alone management mode, departmental LAN management mode, and company LAN management mode.…”
Section: Current Status Of Researchmentioning
confidence: 99%
“…As a consequence, a number of authors have developed systems to automatically recognize the interpersonal stance (often operationalised via the Interpersonal Circumplex) displayed by the user based on social signals. One of the most notable frameworks is presented by Chollet et al [5], who defined a multilayer framework that combines various multi-modal signals: gaze, head orientation, facial expression, dialogue sequences and a computational model to infer interpersonal stance. Although the system covers many modalities, voice is only addressed in a limited sense (i.e., the system uses the moment on which the user is speaking, rather than specific features of the voice).…”
Section: Interpersonal Stance Within Hcimentioning
confidence: 99%